Ответы 1

  • (\sqrt{x} -x+2)*(\sqrt{x} -3)* (\sqrt{x} +3) = 0

    \sqrt{x} - x + 2 = 0

    \sqrt{x} -3 =0

    \sqrt{x} +3 = 0

    x = 1

    x = 4

    x = 9

    x ∈ ∅

    x = 1

    x = 4

    x = 9

    (\sqrt{1} -1+2) * (\sqrt{1} -3) * (\sqrt{1} +3) = 0

    (\sqrt{4} -4 +2) * (\sqrt{4} -3) * (\sqrt{4}+3) = 0

    (\sqrt{9}-9+2) * (\sqrt{9} -3) * (\sqrt{9} +3) = 0

    - 16 = 0

    0 = 0

    0 = 0

    x ≠ 1

    x = 4

    x = 9

    x₁ = 4, x₂ = 9

    • Автор:

      candy
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years